Original paperDoes early insulin treatment decrease the risk of microangiopathy in non-obese adults with diabetes? - Rogowicz, Anita; Litwinowicz, Monika; Piłaciński, Stanisław; Zozulińska, Dorota; Wierusz-Wysocka, Bogna (Archives of Medical Science, 2007)
Introduction: In the clinical practice classification of diabetes type in adult patients is often difficult. In non-obese adults distinguishing between Latent Autoimmune Diabetes in the Adult and type 2 diabetes leads to introduction of different treatment strategies. The aim of the present study was to assess relationship between introduction of insulin therapy at the diagnosis and occurrence of chronic microangiopathic complications of diabetes in non-obese patients aged above 35 years. Material and methods: The group of 71 non-obese patients (BMI <30 kg/m 2 ) with diabetes diagnosed after the age of 35 was estimated. At diagnosis 24 patients were treated with insulin (group A) and 47 patients with oral hypoglycaemics (group B). Results: No significant differences in presence of microangiopathic complications were noted between the groups after 6 years of duration of diabetes. In the multivariate logistic regression analysis, risk factors for the development of any type of diabetic microangiopathy were: longer duration of diabetes (RR 1.12, 95%CI: 1.00-1.27, p=0.04), higher HbA1c value (RR 2.00, 95%CI: 1.21-3.31), and higher BMI (RR 1.25, 95%CI: 0.99-0.25, p=0.048). Moreover the risk factors for microangiopathy were: CRP concentration (RR 1.36, 95%CI: 1.03-1.80, p=0.025) and smoking status (RR 4.37, 95%CI: 1.33-14.44, p=0.013). Conclusions: Initial insulin therapy in non-obese patients with diabetes diagnosed above the age of 35, after 6 years of duration of diabetes, does not decrease significantly the risk of micro and macroangiopathic complications. Main risk factors for development of microangiopathic complications are: longer duration of diabetes, worse metabolic control of diabetes, higher body mass index, higher C-reactive protein (CRP) level and smoking.